MATCHES AND MISMATCHES BETWEEN EFL TEACHERS’ AND STUDENTS’ PREFERENCES FOR CORRECTIVE FEEDBACK IN ENGLISH SPEAKING CLASSES AT A VIETNAMESE UNIVERSITY - Huong, Luu Thi (VNU Journal of Foreign Studies; Vol 36 No 1DO - 10.25073/2525-2445/vnufs.4505, 2020)
This study aimed at examining matches or mismatches between teachers’ and students’ preferences regarding different types of corrective feedback in EFL (English as a foreign language) speaking classrooms at a Vietnamese university. Observation and two parallel questionnaires adapted from Katayama (2007) and Smith (2010) were used to gather data from five EFL teachers and 138 English-majored students. Multiple findings pertaining to each research question were revealed. Overall, results indicated that while there were some areas of agreement between teachers and students, important mismatches in their opinions did occur.